Spiritualitas di Kehidupan Modern dalam Film Animasi Tiongkok Little Door Gods (2016) - Prawira, Mentari Putrirahayu; Haryanto, Haryanto; Bajuri, M. Zahrul Jihadurrohim (Universitas Indraprasta PGRI, 2024)
In contemporary times, rationalism has emerged as the fundamental principle of thinking, leading to the neglect of spiritual matters by society. The portrayal of this concept can be observed in the Chinese animated film called Little Door Gods (2016), helmed by director Gary Wang. This study seeks to examine how the animated film